G-RMOS: GPU-accelerated Riemannian Metric Optimization on Surfaces - Jo, Jeong Won; Gahm, Jin Kyu (Computers in biology and medicine, 2022)
Surface mapping is used in various brain imaging studies, such as for mapping gray matter atrophy patterns in Alzheimer’s disease. Riemannian metrics on surface (RMOS) is a state-of-the-art surface mapping algorithm that optimizes Riemannian metrics to establish one-to-one correspondences between surfaces in the Laplace–Beltrami embedding space. However, owing to the complex calculation with accurate one-to-one correspondences, RMOS registration takes a long time. In this study, we propose G-RMOS, a graphics processing unit (GPU)-accelerated RMOS registration pipeline that uses three GPU kernel design strategies: 1. using GPU computing capability with a batch scheme; 2. using the cache in the GPU block to minimize memory latency in register and shared memory; and 3. maximizing the effective number of instructions per GPU cycle using instruction level parallelism. Using the experimental results, we compare the acceleration speed of the G-RMOS framework with that of RMOS using hippocampus and cortical surfaces, and show that G-RMOS achieves a significant speedup in surface mapping. We also compare the memory requirements for cortical surface mapping and show that G-RMOS uses less memory than RMOS. [Display omitted] •Propose a GPU-accelerated parallel framework for fast surface mapping.•Design a batch scheme with a GPU kernel using instruction level parallelism.•Demonstrate improvement in computational time for brain surface mapping.